Relationship Between Preoperative Anemia and Perioperaive Outcomes Following Posterior Spinal Fusion for Adolescent Idiopathic Scoliosis. (16th November 2020) - Elsamadicy, Aladine A; Freedman, Isaac G; Koo, Andrew B; David, Wyatt; Havlik, John; Reeves, Benjamin; Sarkozy, Margot; Kundishora, Adam; Sciubba, Daniel M; Kahle, Kristopher T; DiLuna, Michael
Abstract: INTRODUCTION: Anemia is one of the most common comorbidities complicating surgical management of adolescent idiopathic scoliosis (AIS) in the pediatric population. METHODS: A retrospective cohort study was performed using the American College of Surgeons National Surgical Quality Improvement Program-Pediatric (NSQIP-P) database from 2016 through 2018. All pediatric patients (age 10 - 18 years) with adolescent idiopathic scoliosis undergoing posterior spinal fusion, or posterior arthrodesis for spinal deformity, were identified using the ICD-10-CM diagnosis and procedural coding system. Patients were then categorized by whether they had recorded baseline anemia or no baseline anemia. Patient demographics, comorbidities, intraoperative variables, complications, LOS, discharge disposition, and reoperation rate were assessed. A multivariate stepwise logistic regression was used to determine the odds ratio for risk-adjusted peri-operative bleed or transfusion, postoperative complication, and extended LOS. RESULTS: A total of 4, 929 patients were identified, of which 592 (12.0%) were found to have preoperative anemia. The Anemic cohort had a higher proportion of female patients and African-American patients than the Nonanemic cohort. The Anemic cohort had a greater prevalence of comorbidities and longer operative times. Compared to the Nonanemic cohort, the Anemic cohort experienced significantly higher rates of perioperative bleed / transfusion (Nonanemic:67.4% vs. Anemic:73.5%, P  = .004) and required greater total amount of blood transfused (Nonanemic:283.2 ± 265.5 mL vs. Anemic:386.7 ± 342.6 mL, P  < .001). The Anemic cohort experienced significantly longer hospital stays (Nonanemic:3.8 ± 2.2 days vs. Anemic:4.2 ± 3.9 days, P  = .001), yet discharge disposition ( P  = .58), 30-day complication rates ( P  = .79), and 30-day unplanned reoperation rates ( P  = .90) were similar between cohorts. On multivariate analysis, anemia was found to be a significant independent predictor of perioperative bleed / transfusion [OR:1.36, 95% CI:(1.12, 1.66), P  = .002] as well as longer hospital stays [RR:0.46, 95% CI: (0.25, 0.67), P  < .001] but was not an independent predictor for postoperative complications ( P  = .85). CONCLUSION: Our study suggests that preoperative anemia may be a risk factor for greater perioperative bleed/transfusion event or a slightly longer length of stay, without greater complication rates in AIS patients undergoing PSF. Anemia thus should not preclude AIS patients from surgical intervention.